Liikunnan ja sukupuolen yhteys mielenterveyteen kouluikäisillä lapsilla ja nuorilla - Brilli, Martin (2025)
Exercise has been recognized as an efficient tool for preventing and treating certain mental health problems and disorders and it also has an important role in preventing and treating chronic diseases. The aim of this study was to investigate if there is association between the change in physical activity and mental health in adolescence and is total physical activity or a specific activity domain more associated with mental health. The sample (n = 239, 108 girls) consisted of children who took part in the Physical Activity and Nutrition in Children (PANIC) study which is a prospective cohort study. The participants were 6–9 years old during baseline measurements and were 15–17 years old after eight-year follow-up period. PA was measured with self-reported questionnaire at baseline and at eight-year follow-up, and mental health was assessed with the PANIC questionnaire, BDI-21 and Finnish version of the Cohen Perceived Stress Scale (PSS-10) at eight-year follow-up. For this study, a sum variable of the previously mentioned mental health test scores was formed to describe overall mental health. The association between physical activity and mental health was analyzed with linear regression analysis. New variables describing the change between the eight-year follow-up and baseline were created to investigate the association between changes in physical activity and mental health. The increase in total PA was inversely associated with depression symptoms and with psychological difficulties (p < 0.05). The increase in total PA and unsupervised PA was inversely associated with stress symptoms and overall mental health. For girls the increase in recess PA was positively associated with stress symptoms, psychological difficulties and overall mental health. For boys the increase in total and unsupervised PA was inversely associated with stress symptoms, psychological difficulties, and overall mental health. For boys the increase in unsupervised PA was also associated with depressive symptoms. For boys the association was inverse in total and unsupervised PA in 8-year follow-up for depressive and stress symptoms, psychological difficulties and overall mental health. For boys recess PA was also associated with psychological difficulties. For girls the association was positive in recess PA for depressive and stress symptoms, psychological difficulties and overall mental health. For girls the increase in recess PA from childhood to youth is associated with higher perceived stress and psychological difficulties. Recess PA was associated with depressive and stress symptoms, psychological difficulties and worse overall mental health for girls in youth. PA was supportive of boys’ mental health. Children and adolescents’ PA and exercising should be supported based on individual preferences and needs because it has a positive impact on their overall wellbeing. More research is needed in children and adolescent sex differences in PA and exercise motivation and perceived meaningfulness.